Water security and its challenges for Malaysia - Malek M.A.; Nor M.A.M.; Leong Y.P. (Institute of Physics Publishing, 2023)
Water Security in Malaysia is a national issue. The Malaysian water services industry faces issues which need to be tackled immediately for it to be viable and sustainable. Among them are the decentralized water services sector, ineffective governance structure, unsustainable tariffs, huge investments required to develop the water supply and sewerage infrastructure, inefficient operation by the operators and high non-revenue water (NRW) losses. In Malaysia, the Sectorial approach embedded in the present water management system and its transformation towards Integrated Water Resources Management (IWRM), is still in a state of inertia. This paper presents the need to transform, from a Supply Management mode (a characteristic of a developing country) to a Water Demand Management mode (a characteristic of a developed country). Issues on Water Demand Management for the Environment which can be a threat to the need for sustainable development for biodiversity are highlighted here. Reliable water accounting systems are found still lacking in this country, especially in the Agriculture and Environmental Sectors, where figures are still highly based on traditional assumptions. Water Quality deterioration remains an issue especially for the Water Supply and Environment Sectors. Available surface water resource is depleting in many regions and states in the Peninsular. Apart from the Reduce, Reuse and Recycle (3R) option for surface water, another option would be to begin a concerted effort for groundwater exploitation. However there are still grey areas of knowledge in the groundwater resources in this country for affirmative decisions and development of appropriate policies. It is also found that, there are no concerted plans to prepare the public for the change from Supply Management to Demand Management. In a developed nation, this change is through stakeholder platforms and supported by appropriate policies, rules and regulations that are based on validated Sciences, Technologies and Innovations (STI). Transforming from Supply Management to Demand Management is a formidable task. This requires the wisdom and knowledge of all experts in the Water Resources Sector. Published under licence by IOP Publishing Ltd.